“‘Youle zee zuch an altrication in him as never was zeen in a brother’: Somerset Dialect in Richard Brome’s ‘The Sparagus Garden’” - Paravano, Cristina (Status Quaestionis, 2017)
The paper proposes to explore the use of south-western stage dialect in The Sparagus Garden (1635) by the Caroline playwright Richard Brome. This dialect has a long tradition on the early modern stage, from Shakespeare and Jonson to Brome. In The Sparagus Garden the dramatist had recourse to south-western stage dialect for multiple reasons: for comic purposes, to portray rustic characters and provide the play with a touch of local colour, but also to discuss social and political issues and to explore questions of identity. What will emerge is how Brome contributed to the development of this stage dialect providing it with a more profound artistic formulation.